Biogenic MnO2 nanoparticles derived from a Cedrus deodara pine needle extract and their composites with polyaniline/activated charcoal as an electrode material for supercapacitor applications. (11th February 2022) - Williams, Linda; Arshad, Mohammed; Rani A. T., Jeeja; Joseph, Abraham
Abstract : A ternary composite of phytogenic MnO2 nanoparticles with polyaniline (PA) and activated charcoal (AC) was designed and fabricated. Abstract : A ternary composite of phytogenic MnO2 nanoparticles with polyaniline (PA) and activated charcoal (AC) was designed and fabricated. The MnO2 nanoparticles were synthesised by a green procedure using an extract of Cedrus deodara pine needles. Polyvinylpyrrolidone (PVP)-stabilized PA was prepared by the oxidative polymerization of aniline employing ammonium persulfate as the oxidising agent in HCl. A binary composite, polyaniline/activated charcoal (PA/AC), was prepared by the polymerisation of aniline in the presence of AC. The as-prepared materials were characterised and their electrochemical measurements exhibited that the ternary composite has a specific capacitance value of 536 F g −1, which is much superior to that of PA/AC (272 F g −1 ) and PA (141 F g −1 ) at 1 A g −1 . Thus, PA/AC/MnO2 was proved to be a promising electrode material for supercapacitor applications.